(untitled) (American Journal of Islam and Society, 2007)
Kecia Ali’s Sexual Ethics and Islam is a fresh and incisive examination of a variety of issues related to marriage and sexuality. Its primary objective is to engage with the values and aspirations of contemporary American Muslims, although it should also find a broad non-Muslim audience in undergraduate courses and among non-specialist readers. Throughout the book, Ali analyzes the concerns of a Muslim community striving both to realize a vision of justice and equality informed by contemporary social realities as well as to cultivate a genuine and honest commitment to Islam’s teachings. Although she sometimes addresses the internal dynamics of the Muslim community (both American and international) in ways that may resonate most with a faith-based audience, non-Muslim readers and students will be fascinated by the degree of Muslim social and theological diversity that she describes. Ali identifies strongly with “progressive” Muslims, although she does not hesitate to critique liberal and conservative orthodoxies. She engages intensively with an emerging canon of English-language progressive Islamic thought, frequently citing such authors as Amina Wadud, Asma Barlas, Khaled Abou El Fadl, Omid Safi, and Farid Esack. One of the book’s striking (and useful) aspects is that it does not assume that the Islamic “center” lies in the Muslim-majority countries of the Middle East or South and Southeast Asia; it unapologetically (and accurately) assumes that the Muslims of North America and other minority communities can produce autonomous and valid developments in Islamic thought and practice. Although her sympathies clearly lie with, for instance, those who would seek to accommodate the religious and personal aspirations of Muslim homosexuals (chapter 5), she also displays an unsparing commitment to internal consistency and intellectual rigor. She neither resorts to easy platitudes about Islam’s egalitarianism and justice nor tolerates them in the arguments of others ...